Intellectualization of traction power supply operation control systems - Damanska, H. O. (Science and Transport Progress, 2010)
In the article the expert management systems on the base of synthesis of heuristic and causal knowledge are offered that allows choosing the energy-saving modes and minimizing the power flow-overs and energy losses in electric-traction networks.